2015
DOI: 10.1007/s11192-015-1607-5
|View full text |Cite
|
Sign up to set email alerts
|

The citation advantage of author-pays model: the case of Springer and Elsevier OA journals

Abstract: Aiming to investigate the citation advantage of author-pays model, the present communication compares open access (OA) and Toll Access (TA) papers recognition in author-pays OA journals in 2007-2011. This is the first large scale study concentrating on all APC-funded OA journals published by Springer and Elsevier as the two greatest publishers authorizing and embracing the model. According to the research findings, the OA papers have been exponentially increased in recent years. They are, also, found to outper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 44 publications
(42 reference statements)
1
37
2
1
Order By: Relevance
“…The articles from high impact factor journals were also chosen in two studies of Norris (30) which researched the OACA in the study of 4,633 articles in the journals of 4 disciplines (ecology, mathematics, sociology and economics). Sotudeh (64) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles from high impact factor journals were also chosen in two studies of Norris (30) which researched the OACA in the study of 4,633 articles in the journals of 4 disciplines (ecology, mathematics, sociology and economics). Sotudeh (64) …”
Section: Resultsmentioning
confidence: 99%
“…Six studies pointed out the OACA (19,30,(63)(64)(65)(66)(67) they evidenced the differences between OACA between the subject fields. Antelman (63) found an increase in citations of OA articles by 45 % in philosophy, 51 % in electrical engineering, 86 % in political science and by 91 % in mathematics.…”
Section: Resultsmentioning
confidence: 99%
“…The purposeful sample consisted of the papers published in the OA journals of Elsevier and Springer from 2007 to 2011, identified by, 19 analyzed at first, last, and corresponding author levels separately.…”
Section: Methodsmentioning
confidence: 99%
“…[8] showed that two of the 11 journals see positive effects on the number of citations due to open access, although the citation advantage appears to weaken over time. [9] [10] stated that the open access advantage in social science humanities disappears when the number of citations of the single most-cited article is eliminated from the data set in [9], suggesting that careful examination of data is needed for analyzing the advantage of open access.…”
Section: Related Literaturementioning
confidence: 99%